Comprehensive analysis of multimedia storytelling in the modern information space - Olga Muravyova4, Asima Ishanova5, Mariyamgul Kussainova1, Lazzat Kozhakhmetova2, Meruert Kumarova3, (Opción, 2019)
The object of this study is multimedia storytelling (as a genre) andits formats in Kazakhstan and French media practice. The theoretical basisof the study was the monographs and scientific articles of Kazakhstan andFrench modern media researchers on new digital formats of journalism asa . As a result, the percentage of stories where there are heroes in the textin the Kazakh and French media is not very different. In conclusion,storytelling’s main characteristics should be considered the obligatorypresence of history on a relevant topic and interpretation of historythrough the prism of the author's perception.